Spinal versus general anaesthesia in percutaneous nephrolithotomy - Wani, Zara; Kumar Harkawat, Dev; Sharma, Meenaxi (International Journal of Medical Research and Review, 2017)
Background: Hemodynamic stability and blood loss reduction are subjects to further consideration in patients undergoing percutaneous nephrolithotomy (PNCL). Objectives: This study compared the preference of spinal anaesthesia (SA) or general anaesthesia (GA) in respect to mentioned concerns. Methods: In this randomized clinical trial, 59 patients who underwent PCNL divided into SA and GA groups. 15-20 mg from intra-thecal bupivacaine 0.5%, and premedication of 0.01-0.02 mg from midazolam, were given to patients in SA group (n = 29). Patients in GA group (n = 30) received premedication of 1-2 μg/kg from fentanyl and 0.01-0.02 mg/kg from midazolam, and intravenously anaesthetized with 100 μg/kg/min of propofol and 0.5 mg/kg of atracurium, given by continuous infusion and N2O/O2 50%. Mean arterial pressure (MAP) and heart rate were recorded intra-operatively and during recovery. Results: MAP and heart rate show no significant differences at designated time points between two groups (P > 0.05). Surgery time, anesthesia time, bleeding volume, and analgesic intake were significantly reduced in SA group (P < 0.05). Conclusions: Regional epidural anaesthesia is an alternative technique for PCNL which achieves more patient satisfaction, less early postoperative pain and less adverse effects from medication with the same efficacy and safety compared to general anaesthesia. It seems that, in patients undergoing PNCL, SA is as effective and safe as GA and with many advantages over it.